PENGOLAHAN BUNGA TELANG (CLITORIA TERNATEA) MENJADI SIRUP DI KELURAHAN BATANG SEROSA, KABUPATEN BENGKALIS SEBAGAI UPAYA MENINGKATKAN UP2K PKK BATANG SEROSA: PROCESSING OF TELANG FLOWER (CLITORIA TERNATEA) INTO SYRUP IN BATANG SEROSA, BENGKALIS REGENCY AS AN EFFORT TO INCREASE UP2K PKK BATANG SEROSA - Rina D’rita Sibagariang; Desi Novita Sari Aritonang; Hanna Peronika Purba; Jordan Roman Riquelme Hutagalung; Mona Oktavia Sihotang; Pasko Andrea Sitanggang; Renata Rosalina Malau; Fictor Agustian; Nova Friska Simanjuntak; Soni Ezra Ridwana Saragih; Rosarindo Harianja (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
Batang Serosa Village is one of the villages in the Bengkalis Regency. The UP2K program, which was implemented in Batang Serosa Village, targeted PKK Batang Serosa women. The selection of PKK as the target for UP2K participants was part of an effort to empower women. Processing telang flower into syrup is an effort to optimize existing natural resources into a useful product as well as having economic selling value. Clitoria Ternatea (CT) or commonly called telang flower comes from the Fabaceae family. Telang flower has been widely used as a natural colorant for food, Telang flower syrup is one form of innovation made. Telang flower itself is known to have health benefits and is widely used as herbal medicine by the community. The UP2K program for PKK women in Batang Serosa Village to process telang flowers into syrup aims to encourage productivity and their participation in developing the economy has been successful through the training program. . As input, for training programs and community empowerment in the future, it is hoped that at the same time it will be able to provide business and marketing training programs as well as control evaluations on a regular basis.